Biomimetic Activator of Sonodynamic Ferroptosis Amplifies Inherent Peroxidation for Improving the Treatment of Breast Cancer. Issue 12 (29th January 2022) - Zhou, Anwei; Fang, Tianliang; Chen, Kerong; Xu, Yurui; Chen, Zhuo; Ning, Xinghai
Abstract: Ferroptosis is a type of nonapoptotic cell death and is gradually emerging as an important anticancer treatment. However, its therapeutic efficacy is impaired by low intracellular levels of reactive oxygen species (ROS) and long‐chain polyunsaturated fatty acids, significantly limiting its therapeutic potential. Herein, a multimodal strategy to improve ferroptosis is presented, in which a state‐of‐art engineered erythrocyte, termed as sonodynamic amplified ferroptosis erythrocyte (SAFE), is developed for simultaneously activating ferroptosis and oxygen‐riched sonodynamic therapy (SDT). SAFE is composed of internalizing RGD peptide and red blood cell membrane hybrid camouflaged nanocomplex of hemoglobin, perfluorocarbon, ferroptosis activator (dihomo‐γ‐linolenic acid, DGLA), and sonosensitizer verteporfin. It is identified that SAFE, under ultrasound stimulation, can not only substantially supply oxygen to overcome tumor hypoxia associated therapeutic resistance, but effectively activate ferroptosis through the coeffect of SDT triggered ROS production and DGLA mediated lipid peroxidation. In vivo studies reveal that SAFE selectively accumulates in tumor tissues and induces desirable anticancer effects under mild ultrasound stimulation. Importantly, SAFE can effectively inhibit tumor growth with minimal invasiveness, resulting in a prolonged survival period of mice. Therefore, a multimodal ferroptosis therapy driven by oxygen‐riched sonodynamic peroxidation of lipids, significantly advancing synergistic cancer treatment, is presented. Abstract : Sonodynamic amplified ferroptosis erythrocyte (SAFE), composed of internalizing RGD peptide and red blood cell membrane hybrid camouflaged nanocomplex of hemoglobin, perfluorocarbon, dihomo‐γ‐linolenic acid and verteporfin, is developed for improving synergistic sonodynamic therapy and ferroptosis. SAFE not only supplies oxygen to overcome tumor hypoxia, but triggers verteporfin to generate reactive oxygen species and amplify inherent peroxidation, thereby effectively inhibiting tumor growth.